Whole-genome sequencing reveals transmission pattern and drug resistance of Mycobacterium tuberculosis intra- or inter-hosts - Ding, Feng; Liu, Wanfei; Wu, Chi; Zhang, Wensi; Chen, Shuyan; Lai, Wenjie; Qu, Jiayao; Lin, Qiang; Lu, Shuihua; Qu, Jiuxin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundTuberculosis (TB) remains a serious global public health problem. The Mycobacterium tuberculosis (MTB) is responsible for approximately 10 million new TB cases globally each year. This study aimed to investigate transmission pattern and drug resistance of MTB in Shenzhen, China.MethodsA retrospective study on 286 samples from 184 TB patients collected between 2015 and 2018 in Shenzhen Third People’s Hospital was conducted using whole-genome sequencing. Drug susceptibility testing (DST) was performed using both phenotypic DST (pDST) and molecular DST (mDST). Sample diversity was evaluated by SNPs and transmission clusters were identified based on SNP differences of 12 or fewer in genetic clusters.ResultsExcept four samples identified as non-tuberculous mycobacteria, 282 MTB samples (181 patients) underwent mDST, with 244 samples (162 patients) undergoing pDST. The overall multidrug-resistant rate in patients was 22.31% in pDST (12.00% for new patients and 40.82% for retreatment patients) and 34.48% in mDST (20.41% for new patients and 58.21% for retreatment patients). Totally 92 transmission clusters were identified, encompassing 70.21% samples (57.46% patients), with 5 clusters containing samples (15, 5.32%) from different patients (9, 4.97%), indicating recent transmission. The drug-resistant mutations in 36 of 45 transmission clusters (80.00%) were identical in all samples, suggesting the transmission of drug resistance. Patients with multiple samples were categorized into simultaneous sampling (SS) and continuous sampling (CS) groups, revealing significant differences in treatment types, treatment outcomes, residential addresses, and drug resistance types. mDST showed greater accuracy than pDST in SS and CS groups. A novel method based on heterozygous SNPs and two-sample Kolmogorov–Smirnov test were developed and identified 12 (4.26%) samples as mixed infection samples. Six of 12 patients had mixed and pure samples together, and major strains of mixed samples were closer to corresponding pure strains than minor strains.ConclusionsThis retrospective study, conducted at the only municipal hospital specializing in infectious diseases in Shenzhen, provides the opportunity to understand drug resistance of TB patients, which mainly are refractory patients. The study revealed transmission patterns of MTB, analyzed mixed infections, and tracked changes in MTB strains during short/long-term treatment.